PERBANDINGAN KINERJA PORTOFOLIO SAHAM BUMN YANG TERDAFTAR DI INDEKS BISNIS-27 MENGGUNAKAN MODEL SHARPE, TREYNOR, DAN JENSEN - Friska Dayanti Nadeak; Trisnani Indriati; Dian Riskarini (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2022)
Bisnis-27 Index from 2017 to 2020. The optimal portfolio uses Single Index Model, while its performance measurement uses Sharpe, Treynor, and Jensen Models. The data analysis technique used to answer the research hypothesis is One-way Anova test followed by comparing the averages using Post-hoc test LSD and Tukey HSD. Five of the six stocks sample became optimal portfolio and the three measurement models of portfolio performance show a positive number which means the portfolio is performing well. The hypothesis test results show a difference in the values from the three measurement models, then the Post-hoc test shows a significant difference between the Sharpe and Jensen Models.